Experiences That Matter: Unraveling the Link Between Extracurricular Activities and Emotional and Social Competencies - Cortellazzo, Laura; Bonesso, Sara; Gerli, Fabrizio; Pizzi, Claudio (Frontiers in Psychology, 2021)
Emotional and social competencies have been shown to be extremely desirable in young people for successful entry into the labor market. Their development has been primarily studied as result of formal training in the educational and work domains, whereas relatively little is known about the role played by extracurricular activities in promoting this type of competencies. Non-working personal experiences are often used as proxies to assess the emotional and social competencies of candidates in recruitment and selection phases. However, this inference is not based on clear scientific evidence. Drawing on experiential learning theory, this study investigates empirically the relationship between a range of extracurricular activities (volunteering, cultural activities, experience abroad, sport) and the competency portfolio of graduates. Data were collected from a sample of 324 graduates through a structured survey and a multi-rater assessment of their emotional and social competencies. The results of the Partial Least Square-Path Modeling in general provide support for the positive association between experiential extracurricular activities and emotional and social competencies, although not all relationships are supported. The present study contributes to advance the understanding of the determinants of emotional and social competencies examining the relationship with a broad range of extracurricular activities. Moreover, it discusses implications for higher education and human resource management.